Mobile city : emerging media, space, and sociality in contemporary Berlin - Kraemer, Jordan H., 1978- (Ithaca : Cornell University Press, 2024)
"In late-aughts Berlin, emerging media, from Facebook to smartphones, reworked place-based identities, facilitating urban, middle-class aspirations to cosmopolitan connection while transforming experiences of everyday life. These scalar transformations were lived out through ordinary practices that reconfigured sociality, mobility, and urban space"--
Introduction : Mobile Berlin -- Locating Emerging Media -- Multiscalar Mobilities -- Multiscalar Publics -- Networked National Feelings -- Scaling Media Infrastructures -- Public Media in Urban Space -- Epilogue : Illiberal Spaces.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 09, 2025).
JSTOR
Keywords: Social media and society -- Germany -- Berlin -- History -- 21st century; Online social networks -- Germany -- Berlin -- History -- 21st century; Digital media -- Social aspects -- Germany -- Berlin; City and town life -- Germany -- Berlin -- History -- 21st century; Social change -- Germany -- Berlin -- History -- 21st century; Place attachment -- Social aspects -- Germany -- Berlin; Spatial behavior -- Social aspects -- Germany -- Berlin; Group identity -- Germany -- Berlin -- History -- 21st century; Berlin (Germany) -- Social conditions -- 21st century; Berlin (Germany) -- Social life and customs -- 21st century; Vie urbaine -- Allemagne -- Berlin -- Histoire -- 21e siècle.; SOCIAL SCIENCE / Media Studies